Implementation of Recommendations Results Post-Accreditation of Health Centers in Sumenep Regency Towards Pall Accreditation - Yuly Peristiowati; Ida Winarni (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Health development is an integral and most important part of national development. Puskesmas is a leading service unit and can directly reach the community, carry out health services. Accreditation aims to assess the quality system and service system in Puskesmas and other First Level Health Service Facilities. Puskesmas are required to be able to guarantee quality improvement, performance improvement and the implementation of risk management that is carried out on an ongoing basis, so it is necessary to carry out an assessment through an accreditation mechanism. The Guluk Guluk Health Center in Sumenep Regency has carried out the Accreditation process 2 times, namely in 2016 with Basic Accredited status and 2019 Plenary Accredited. From this, this research was carried out with the title Implementation of Recommendations Results of Post-Accreditation of Health Centers in Sumenep Regency Towards Plenary Accreditation. The purpose of this study was to explore the implementation of the recommendations of the Post-Accreditation of Puskesmas in Sumenep Regency towards Plenary accreditation. The thematics are categorized and are Follow-up Planning, Implementation of Recommendations, Implementation Checks and Implementation Improvements. The results of the study indicate that the Guluk Guluk Health Center has tried to make recommendations from the Accreditation Commission in the framework of continuous quality improvement.